Influence of rotor blade scaling on the numerical simulation of a high pressure gas turbine - Lastiwka, Derek (University of Ottawa (Canada), 2009)
Rotor blade scaling is a method aimed at reducing the computational domain in turbomachinery simulations by changing the number of blades such that the blade-to-vane ratio in the scaled geometry is equal to the ratio of two small integers (e.g., 1/1, 1/2, 1/3, 2/3, 3/4 etc.), but without changing the airfoil shape. The objective of this study is to determine the quantitative effects that rotor blade scaling has on the numerical simulations of a representative single-stage gas turbine, with particular focus on parameters that influence vibratory stresses on the rotor blades. Simulations were conducted using the commercial software FLUENT 6.3.26. Results from an unsealed case were compared to LDV measurements and to two scaled cases. Average computing times for the three cases confirmed that the cases with the smallest computational domain were the most efficient. The present results demonstrate that blade scaling affects significantly the magnitude of unsteady pressure fluctuations, which influence the level of vibratory stresses on the blades. Moreover, scaling has been found to affect the size of blade wakes and the magnitude of losses in the blade wakes. As the rotor blade size increased pressure fluctuations on the surface of the rotor blade increased. Pressure fluctuations on the surface of the stator vane decreased as the blade to vane ratio more closely approached an integer number. These results suggest that, in numerical simulations of gas turbine operation, scaling should be kept to very low levels to avoid strong departures from the predicted performance of the unsealed geometry. The present work addresses the interest of the aerospace industry in using standardized CFD tools and reducing computational time without seriously compromising simulation accuracy.
Keywords: Engineering, Mechanical.